PENGGUNAAN PADANAN KOSAKATA BAHASA INDONESIA PADA GENERASI MILENIAL - Nanda Saputra; Nurul Aida Fitri (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2020)
The increasing use of foreign terms among the millennial generation has reduced the use of their Indonesian equivalents. This study aimed to describe the mastery of Indonesian vocabulary equivalents among students and university students. The study employed a qualitative approach within a sociolinguistic framework. Data were collected through a questionnaire containing 35 foreign terms, for which respondents were asked to provide the Indonesian equivalents. The respondents consisted of students from MAS Unggul Nurur Rasyad Al-Aziziyah Tijue and undergraduate students of the Primary Teacher Education Program at STIT Al-Hilal Sigli. The data were analyzed using the translational equivalent method. The findings revealed that high school students correctly identified the Indonesian equivalents of 9 terms, partially mastered 3 terms, and failed to identify 23 terms. Meanwhile, university students correctly identified 13 terms, partially mastered 6 terms, and failed to identify 16 terms. These findings indicate that the mastery of Indonesian vocabulary equivalents among the millennial generation remains relatively low. Therefore, greater efforts are needed to strengthen the use of proper Indonesian through education and daily language practices.